2022
DOI: 10.3389/fpubh.2022.1063429
|View full text |Cite
|
Sign up to set email alerts
|

Health behavior interventions for university students measuring mental health outcomes: A scoping review

Abstract: IntroductionMany university students have poor mental health, and co-occurring health risk behaviors. Targeting health behavior change in this population may improve mental health outcomes. This scoping review describes the extent and range of randomized controlled trials (RCT) evaluating interventions targeting health risk behaviors and measuring a mental health outcome, among university students.MethodsSix electronic databases were searched for RCTs published until the 18th May 2021. Eligible RCTs included u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…In addition, few studies have examined sleep, physical activity, and screen time in the young Brazilian university population during the pandemic (Stockwell et al, 2021). It's important to consider that university students are particularly susceptible to irregular sleep patterns and stress due to the demands of academic and social life, making them a population at risk for experiencing negative mental health symptoms (Hutchesson et al, 2023). Despite the existing extensive literature about the impact of the COVID-19 pandemic on health, there are still gaps related to physical and mental health of university students.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, few studies have examined sleep, physical activity, and screen time in the young Brazilian university population during the pandemic (Stockwell et al, 2021). It's important to consider that university students are particularly susceptible to irregular sleep patterns and stress due to the demands of academic and social life, making them a population at risk for experiencing negative mental health symptoms (Hutchesson et al, 2023). Despite the existing extensive literature about the impact of the COVID-19 pandemic on health, there are still gaps related to physical and mental health of university students.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention in relation to mental ill-health also encompasses other health behaviours (eg, dietary health, physical activity, sleep) that can have an impact on mental health outcomes. 21 Harnessing common practice elements can enable an evidence-informed approach to prevention even when a specific evidence-based intervention may be lacking (as may be the case in many LMIC settings where this research area is less developed). 17 22 …”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned aspects serve to highlight the need for a scoping review to help clarify concepts and definitions, summarise the results of existing studies, identify critical factors and detect gaps in the literature 11 12. Although there are previous reviews, they all refer to specific health promotion contexts or interventions 13 14. Thus, for example, an umbrella review of interventions on health risk behaviours in students conducted by Hutchesson et al 13 revealed a moderate volume of experimental research on university students’ mental health.…”
Section: Introductionmentioning
confidence: 99%
“… 11 12 Although there are previous reviews, they all refer to specific health promotion contexts or interventions. 13 14 Thus, for example, an umbrella review of interventions on health risk behaviours in students conducted by Hutchesson et al 13 revealed a moderate volume of experimental research on university students’ mental health. Another review aimed at providing an overview of artificial intelligence technologies in elderly healthcare by Ma et al 14 showed the great potential of artificial intelligence technologies in elderly healthcare.…”
Section: Introductionmentioning
confidence: 99%